Involvement of Penicillium digitatum PdSUT1 in fungicide sensitivity and virulence during citrus fruit infection - De-Ramón-Carbonell, Marta; Sánchez-Torres, Paloma (2018)
A putative sucrose transporter PdSUT1 included in the same clade that Sutlp from Schizosaccharomyces pombe was identified in Penicillium digitatum, the major citrus postharvest pathogen. PdSUT1 gene was characterized using target gene disruption and gene overexpression. The Delta PdSUT1 mutants generated by gene elimination showed reduction in fungal virulence during citrus fruit infection assayed in mature fruit at 20 degrees C. However, the overexpression mutants did not increased disease severity neither in the mutants coming from a high virulent nor from a low virulent P. digitatum progenitor strains. Moreover, fungicide sensitivity was affected in the deletant mutants but not in the overexpression transformants. The expression analysis of several genes involved in fungicide resistance showed an intensification of MFS transporters and a decrease of sterol demethylases transcriptional abundance in the Delta PdSUT1 mutants compare to the parental wild type strain. PdSUT1 appear not to be directly involved in fungicide resistance although can affect the gene expression of fungicide related genes. These results indicate that PdSUT1 contribute to P. digitatum fungal virulence and influence fungicide sensitivity through carbohydrate uptake and MFS transporters gene activation.